The Influence of Knowledge and Attitudes on Clean and Healthy Living Behavior in Class V and VI Students at SD Negeri 8 Simpang Rimba South Bangka Regency in 2023 - Hanjiansyah, Mico; Fajrianti, Gita; Dwibarto, Rendita; McArthur, Max (Jurnal Ilmiah Kesehatan, 2024)
Students are the primary assets for future development, and their health must be prioritized and protected. A significant portion of children's health issues stem from unhealthy behaviors within the school environment. Promoting clean and healthy living behaviors in schools is an initiative aimed at enhancing the awareness of school residents to prevent diseases and create a hygienic environment. This initiative should be based on the knowledge and attitudes of each student. The objective of this research was to investigate the influence of knowledge and attitudes on clean and healthy living behaviors among class V and VI students at SD Negeri 8 Simpang Rimba, South Bangka district. The research design employed was cross-sectional. The population comprised 171 respondents, with a sample of 71 respondents, including 31 from class V and 40 from class VI. Univariate data analysis and multiple linear regression tests were conducted. The impact of student knowledge and attitude variables on clean and healthy living behavior was assessed through T-tests. The results indicated that the T-test values (2.357 > 1.666 and 2.044 > 1.066) with corresponding p-values (0.021 < 0.05 and 0.045 < 0.05) suggested a significant influence. The calculated F-test (5.019 > 3.128) further supported the significance of the overall influence, with an F significance value (0.009 < 0.05) below the alpha level. In conclusion, there is a positive combined influence of knowledge and attitudes on clean and healthy living behavior among class V and VI students at SD Negeri 8 Simpang Rimba, South Bangka district in 2023.